Induced Earthquake Families Reveal Distinctive Evolutionary Patterns Near Disposal Wells. Issue 9 (28th September 2018) - Cochran, Elizabeth S.; Ross, Zachary E.; Harrington, Rebecca M.; Dougherty, Sara L.; Rubinstein, Justin L.
Abstract: The timing of events in seismic sequences can provide insights into the physical processes controlling fault slip. In southern Kansas, the rate of earthquakes rose rapidly starting in 2013 following expansion of energy production into the area, demanding the disposal of large volumes of wastewater into deep wells. Seismicity catalogs that are complete to low magnitudes can provide insights into the physical processes that induce seismicity near wastewater disposal. We develop a catalog of over 130, 000 earthquakes recorded in southern Kansas from mid‐March 2014 through December 2017 by applying a matched filter algorithm to an original catalog of 5, 831 template earthquakes. Detections have nearly identical waveforms to their associated template event and represent slip on nearly co‐located sections of a fault. We select template events with at least 100 associated detections and examine the characteristics of these prolific families of earthquakes. We find that families located close (<10 km) to areas with significant volumes of injected fluids have near‐Poissonian interevent times and the families remain active over longer durations. Families farther from high‐volume injection wells show strong clustering of interevent times and shorter sequence durations. We conclude that increasing pore fluid pressures from nearby disposal of large volumes of wastewater is the primary driver of these long duration episodes, with earthquake‐earthquake interactions driving sequences at greater distance from the wells. Key Points: Near‐repeated earthquake families close to disposal wells show different interevent time evolution than those at greater distances Families near wells show near‐Poissonian interevent times, while families at greater distances are more highly clustered Increasing pore‐fluid pressures likely controls the timing of earthquake sequences close to wells